The complete chloroplast genome of Holboellia angustifolia (Ranales: Lardizabalaceae), a traditional herbal species - Xiaozhu Wu; Tongjian Li; Feng Wen (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome of Holboellia angustifolia was 157,797 bp in length, displayed a typical quadripartite structure, composed of a LSC region of 86,543 bp and a SSC region of 18,972 bp, separated by a pair of IRs of 26,141 bp each. The chloroplast genome contains 130 genes, consisting of 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Fifteen genes have one intron, and 3 genes contain two introns. The overall A/T content in the chloroplast genome of H. angustifolia was 61.31%. Phylogenetic analysis showed that H. angustifolia was closely related to Holboellia latifolia.